2018
DOI: 10.3390/su10082634
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Pollutograph by Prediction Indices: An Evaluation in Several Urban Sub-Catchments

Abstract: A generalized methodology applicable to any urban sub-catchment to calculate the pollution curve due to combined sewer overflows would help to implement integrated management policies to reduce urban impacts on the environment. An existing methodology to predict the pollutographs associated to rainfall events is tested in five different sub-catchments with very different pluviometry. Ninety-three rainfall events have been considered by measuring the in-sewer turbidity along the runoff episodes. Such data is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Er (%) all storm events VanSickle and Beschta [2] modified 9.0% Garcia et al [3,4] Figure 12 presents the cumulative event suspended sediment, ESS, in tons for the period of study for all 27 storm events. It may be concluded that, in general, all the models proposed at the annual scale are able to reproduce the measured values of SSC for the storm events.…”
Section: Sediment Transportmentioning
confidence: 99%
See 4 more Smart Citations
“…Er (%) all storm events VanSickle and Beschta [2] modified 9.0% Garcia et al [3,4] Figure 12 presents the cumulative event suspended sediment, ESS, in tons for the period of study for all 27 storm events. It may be concluded that, in general, all the models proposed at the annual scale are able to reproduce the measured values of SSC for the storm events.…”
Section: Sediment Transportmentioning
confidence: 99%
“…The final two variables, DWP and PEEV, were not previously included in the proposed models and constitute a novelty when applying these models. Van Sickle and Bechsta [2] Garcia et al [3,4] Shear stress based model The importance of the present work is based on the recognition that, to model the suspended sediment concentration during different storm events, the following has to be taken into account: the quantity of fine sediments existing in the bed at the initiation of the storm event and how consolidated these sediments are. This is done through the following measurable variables: the existing fine sediment volume stored in the bed, S(t−1); the period between storm events, DWP; and the volume eroded during the previous event, PEEV.…”
Section: Sediment Transportmentioning
confidence: 99%
See 3 more Smart Citations